Supporting transgender autistic youth and adults : a guide for professionals and families - Gratton, Finn V. (Jessica Kingsley Publishers, 2020)
Providing advice on how professionals working with autistic trans youth and adults can tailor their practice to best serve their clients and how parents can support their trans autistic children, this book increases awareness of the large overlap between trans identities and autism. By including chapters on gender diversity basics, neuroqueer trauma and how to support neuroqueer individuals, this book sets out strategies for creating more effective support that takes into account the unique experiences of trans people on the spectrum. Written by a therapist who identifies as neuroqueer, this book is the perfect companion for professionals who want to increase their knowledge of the experiences and needs of their trans autistic clients.